Psychiatrische geschiedenissen - Gijswijt-Hofstra, M.; Oosterhuis, H. (BMGN - Low Countries Historical Review, 2001)
G. Dimmendaal, Heropvoeding en behandeling. Meisjes in Huize de Ranitz, Groningen 1941-1967 G. Blok, J. Vijselaar, Terug naar Endegeest. Patiënten en hun behandeling in het psychiatrisch ziekenhuis Endegeest 1897-1997 H.G.M. Rooijmans, Negenennegentig jaar tussen wal en schip. Geschiedenis van de Leidse universitaire psychiatrie (1899-1998) E. Tonkens, Het zelfontplooiingsregime. De actualiteit van Dennendal en de jaren zestigPsychiatric HistoriesA great number of historical works on psychiatry and mental health care in the Netherlands have appeared in the last decade. Most of these works concern the twentieth century. In this review-article these books and some recent historiographical trends are discussed. Histories of mental asylums and hospitals make up the largest single category. Other themes covered by historical studies are academic, social and forensic psychiatry, ambulatory mental health care, psychoanalysis and psychotherapy, the relationship between psychiatry and religion, antipsychiatry, the role of patients,specific mental disorders and the wider social and cultural context. Two types of historiography can be distinguished: works which have been commissioned by psychiatric institutions (memorial books) and academic studies. The first group — apart from some recent memorial books —- tends to be fairly factual and descriptive, whereas the second one is more analytical and sociological. The article concludes by pointing to some gaps in historical research and offering prospects for future research.